Farewell to Naples: Ferrante’s 'Story of a New Name' - Palma, Pina (Forum Italicum: A Journal of Italian Studies, 2018)
In Ferrante’s Story of a New Name, the protagonist’s journey to self-knowledge and self-realization is mapped through a farewell trip to Naples before she begins her studies in Pisa. As the centerpiece and background around and against which Elena’s accomplishments, failures, and societal pressures revolve, Naples emerges as a mosaic of energy and lethargy, unbreakable traditions and negligible innovations. While these elements mirror the protagonist’s powerlessness in changing the “norms” to which she is expected to adhere, they also function as her spur to a steady shift toward self-understanding. In this article, I analyze the ways in which Ferrante’s use of the beauty and lure, corrosiveness and lethality of Naples parallel her discourse on the protagonist’s search for self-understanding, a process that will ultimately enable Elena, the protagonist, to find self-realization. © 2018, The Author(s) 2018.
Keywords: authorship; dept.wll; labyrinth; memory; peer-reviewed; reading; self-fulfillment; self-knowledge; urban space

Savoring Power, Consuming the Times: The Metaphors of Food in Medieval and Renaissance Italian Literature - Palma, Pina (University of Notre Dame Press, 2013)
"Pina Palma's Savoring Power, Consuming the Times: The Metaphors of Food in Medieval and Renaissance Italian Literature is an innovative look at the writings of five important Italian authors--Boccaccio's Decameron, Pulci's Morgante, Boiardo's Innamorato, Ariosto's Furioso, and Aretino's Ragionamento. Through the prism of gastronomy, Palma examines these key works in the Western literary canon, bringing into focus how their authors use food and gastronomy as a means to critique the social, political, theological, philosophical, and cultural beliefs that constitute the fabric of the society in which they live." -- Publisher's website.
Keywords: 16th century; History and criticism; Food in literature; Gastronomy in literature; History and criticism; Italian literature; Italian literature; SCSU Faculty Scholar Award; To 1400; award_winner; dept.wll; faculty_collection

The devil and the mirror: Pulci’s theology - Palma, Pina (Luigi Pulci in Renaissance Florence and Beyond, 2018)
Keywords: dept.wll